Post-mortem and symbiotic sabellid and serpulid-coral associations from the lower cretaceous of Argentina - Garberoglio, R.M. (2011)
One morphotype of sabellids (Sabellida, Sabellidae) and two of serpulids (Sabellida, Serpulidae), found as encrusters on scleractinian ramose corals of the species Stereocaenia triboleti (Koby) and Columastrea antiqua Gerth, from the Agrio Formation (early Hauterivian) from Neuquén Basin, Argentina, are described. The identified morphotypes, Glomerula lombricus (Defrance), Mucroserpula mucroserpula Regenhardt and Propomatoceros sulcicarinatus Ware, have been previously recorded from the Early Cretaceous of the northern Tethys. Two different type of sabellid and serpulidcoral associations have been recognized. The first and more abundant association corresponds to post-mortem encrustation on corals branches. The second one corresponds to a symbiotic association between the serpulid P. sulcicarinatus and both species of corals. The serpulid tubes are recorded parallel to the coral branches reaching the upper tip of them and they were bioimmured within the coral as they grew upwards. The studied symbiotic relationship between serpulids and corals may be regarded as a mutualism as both members probably benefited each other. This type of association has similarities with recent cases of symbiosis between serpulids and corals, but had no fossil record until now. © 2011 by the Sociedade Brasileira de Paleontologia.